2020
DOI: 10.3389/fgene.2020.00257
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of the Mitochondrial Genomes of Nicotiana tabacum: Hints Toward the Key Factors Closely Related to the Cytoplasmic Male Sterility Mechanism

Abstract: Background: Cytoplasmic male sterility (CMS) is a complex phenomenon of plant sterility that can produce non-functional pollen. It is caused by mutation, rearrangement or recombination in the mitochondrial genome. So far, the systematic structural characteristics of the changes in the mitochondrial genome from the maintainer lines to the CMS lines have not been reported in tobacco. Results: The mitochondrial genomes of the flower buds from both CMS lines and maintainer lines of two Nicotiana tabacum cultivars … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 57 publications
3
7
0
Order By: Relevance
“…Thus, the divided subgenome might be more common in plants [ 60 ]. In our study, we confirmed the existence of alternative conformations, and previously, this low-frequency recombination has been reported to have certain effects on plant growth, such as the induction of cytoplasmic male sterility (CMS) [ 61 , 62 ].…”
Section: Discussionsupporting
confidence: 90%
“…Thus, the divided subgenome might be more common in plants [ 60 ]. In our study, we confirmed the existence of alternative conformations, and previously, this low-frequency recombination has been reported to have certain effects on plant growth, such as the induction of cytoplasmic male sterility (CMS) [ 61 , 62 ].…”
Section: Discussionsupporting
confidence: 90%
“…In many seed plants, rearrangement endpoints in organellar genomes are often associated with repeats ranging in size from tens to hundreds of nucleotides (Marechal & Brisson, 2010; Cole et al ., 2018; Mower & Vickrey, 2018; Wu et al ., 2021). Moreover, operons are more tightly maintained in the plastome (Cui et al ., 2006; Wicke et al ., 2011) than in the mitogenome (Liu et al ., 2020; Wang et al ., 2020). Finally, we speculate that, in plant mitogenomes, the rearrangements themselves may be an adaptive phenomenon, potentially serving as a mechanism to prevent runaway size expansion.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, repeats of hundreds to thousands of base pairs are abundant in plant mitogenomes (Wynn & Christensen, 2019), whereas in the plastome, repeats > 100 bp are generally absent except for the single large inverted repeat (Mower & Vickrey, 2018). In many seed plants, rearrangement endpoints in organellar genomes are often associated with repeats ranging in size from tens to hundreds of nucleotides (Marechal & Brisson, 2010;Cole et al, 2018;Mower & Vickrey, 2018;Wu et al, 2021) New Phytologist the plastome (Cui et al, 2006;Wicke et al, 2011) than in the mitogenome (Liu et al, 2020;Wang et al, 2020). Finally, we speculate that, in plant mitogenomes, the rearrangements themselves may be an adaptive phenomenon, potentially serving as a mechanism to prevent runaway size expansion.…”
Section: Explanations For the Increased Mitogenomic Rearrangement In ...mentioning
confidence: 99%
“…sequences, and introns, the third-generation sequencing technology with PacBio library (8-10 kb) was used to sequence both CMS lines and maintainer lines of two Nicotiana cultivars (YY85, sYY85, ZY90, and sZY90), 16 CMS specific ORFs with three (orf91, orf115b, and orf100) ever reported were screened (Wang et al, 2020;Zheng et al, 2018).…”
Section: Core Ideasmentioning
confidence: 99%